Dyslexia, literacy and inclusion child-centred perspectives - MacBlain, Sean; Long, Louise; Dunn, Jill (SAGE, 2015)
"This book is about raising standards in literacy for children with dyslexia by putting the child at the centre of everything you do, focusing on wellbeing, and recognising the role that adults have to play in ensuring all children reach their potential."--Provided by publisher.